Educational aspirations and social development in the novel Aziman Anak Yatim (1965) by Mohd. Aris Bahnan - Mohd Hanafiah, Halis Azhan; Othman, Shamsudin; Abdullah, Muhammad Alif Redzuan (Human Resource Management Academic Research Society, 2024)
This study was conducted to examine the educational aspirations and social development in the novel Aziman Anak Yatim (1965) by Mohd. Aris Bahnan. The novel revolves around the perseverance of an orphaned and impoverished boy in realizing his dream of becoming a medical doctor in the 1960s. This study outlines three objectives to be achieved. First, to identify the depiction of a child character striving to achieve educational and social development aspirations in the novel Aziman Anak Yatim by Mohd. Aris Bahnan. Second, to analyze the actions taken to achieve educational and social development aspirations by the child character in the novel Aziman Anak Yatim by Mohd. Aris Bahnan. Third, to synthesize the relationship between external changes outside the text and the educational and social development aspirations found in the novel Aziman Anak Yatim by Mohd. Aris Bahnan. This study utilizes the Genetic Structuralism Theory to achieve these three objectives. The study’s findings reveal that the child character in the novel, Aziman, works diligently with the determination to become a medical doctor, thus escaping the grip of poverty. To achieve this goal, the character of Aziman fully takes advantage of the government's educational and social development plans in line with the advancements made after Malaysia gained its independence.